The Comparation Between Plyometrics and Aerobic Exercise on Medical Student’s Mood in Diponegoro University - Karoni Karoni; Muflihatul Muniroh; Marijo Marijo; Endang Kumaidah (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Physical activity is important to do because a sedentary lifestyle is one of the causes of various health problems in the world. One of the importance of physical activity is to improve mental health, quality of life and well-being. Physical activity significantly has a positive impact on a person's mood. Plyometrics and aerobic exercises are popular physical activities, but comparing the effects of both in improving cognitive function, especially in the mood domain, has never been done. Objective: To analyze mood differences between the group with plyometrics exercise and the group with aerobic exercise in students of the Faculty of Medicine, Diponegoro University.Methods: This study is an experimental study with parallel 3 groups pre and post-test design. The research subjects were 45 UNDIP medical students who were selected by purposive sampling and grouped into 3 groups randomly. The untreated control group (n = 15), the plyometrics treatment group (n =15), and the aerobic treatment group (n = 15). The treatment group did physical activity for 6 weeks. Mood levels were measured before and after the intervention using the Profile Of Mood States (POMS). The better a person's mood, the lower the Total Mood Disorder (TMD) score is obtained.Results : TMD scores (pre-test to post-test) in the plyometrics (p <0.001) and aerobic (p = 0.001) groups both experienced a significant decrease. However, there was no significant difference between the TMD post-test scores in the plyometrics treatment group and the aerobic treatment group.Conclusion: Plyometrics and aerobic exercise has a similar effect on improving mood score.